Small Intestinal Bacterial Overgrowth: Clinical Features and Therapeutic Management. Issue 10 (October 2019) - Rao, Satish S. C.; Bhagatwala, Jigar
Abstract : Small intestinal bacterial overgrowth (SIBO) is a common, yet underrecognized, problem. Its prevalence is unknown because SIBO requires diagnostic testing. Although abdominal bloating, gas, distension, and diarrhea are common symptoms, they do not predict positive diagnosis. Predisposing factors include proton-pump inhibitors, opioids, gastric bypass, colectomy, and dysmotility. Small bowel aspirate/culture with growth of 10 3 –10 5 cfu/mL is generally accepted as the "best diagnostic method, " but it is invasive. Glucose or lactulose breath testing is noninvasive but an indirect method that requires further standardization and validation for SIBO. Treatment, usually with antibiotics, aims to provide symptom relief through eradication of bacteria in the small intestine. Limited numbers of controlled studies have shown systemic antibiotics (norfloxacin and metronidazole) to be efficacious. However, 15 studies have shown rifaximin, a nonsystemic antibiotic, to be effective against SIBO and well tolerated. Through improved awareness and scientific rigor, the SIBO landscape is poised for transformation.